Experimental Studies of Heat and Moisture Exchange in the Process of Convective Drying of Thin Wet Materials - A. I. Ol’shanskii; S. V. Zhernosek; A. M. Gusarov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
New ways of experimental data processing by generalized complex variables that are characteristic of the drying process are presented. The authors presented the results of a study of heat and moisture exchange in the convective drying of thin flat moist capillary-porous materials. As a result of the processing of the experimental data, equations were obtained for determining the densities of heat fluxes, average integral temperatures, drying time and moisture evaporation rate in the second drying period. The relationship between the densities of heat fluxes in the first and second periods and the temperature change in the second period is revealed. The dependence for calculating the temperature of the material in the period of the falling drying rate taking into account the heat that is expended to heat the wet body is presented. The equations for determining the temperature in the second period by the temperature coefficient of drying, the rate of heating of the wet material and the rate of heating of the wet body are presented as well. An equation for determining the drying time by the value of the rate of loss of moisture content of the material is given. A mathematical expression for calculating the intensity of moisture evaporation in the first and second drying periods depending on the ratio of moisture content in the first period and the current in the second moisture content one is set. The conditions of a regular regime for heat and moisture exchange for a second drying period are adduced. The authors consider the possibility of determining the rate of heating of wet material by the heating rate using the graphical differentiation of the temperature function, which is described by the curve, as a function of time in the second drying period. The problems of using the methods of the theory of the regular regime for heating wet bodies during the investigation of the drying process are considered. The formulas for determining the rate of heating of the body and the rate of loss of moisture content are given. The accuracy of the experimental data processing and the reliability of the experimental equations obtained for all the materials under study are verified. As a result of the research, all the basic kinetic characteristics necessary for the calculation of heat and moisture exchange in the drying process have been determined.